DAMPAK STRATEGI DUAL SAFEGUARD WEB-BASED INTERACTIVE (DGWI) DENGAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI SUHU DAN KALOR - Elfa Ma’rifah; Parno Parno; Nandang Mufti (Graduate School of Universitas Negeri Malang, 2016)
This study aims to determine differences in students' mastery of concepts before and after learning through DGWI strategy with PBL models in matter Temperature and Heat. The study was conducted in SMA Negeri 4 Malang with a sample of 31 students. Data analysis techniques in this study using the different test with paired samples t-test. The results showed there are differences between the students' mastery of concepts before and after learning through DGWI strategy with PBL models. The average student mastery of the concept of pre-test is higher than the post-test, which increased from 41.955% to 69.637% with effect size d-value of 2.667 (trong) and N-gain categorized